ANALISIS KRITIS PENGEMBANGAN KAWASAN TERPADU DI BUMI SERPONG DAMAI (BSD) DALAM PERSPEKTIF PROYEK STRATEGIS NASIONAL - Hermawan; Martin Roestamy (JURNAL ILMIAH LIVING LAW, 2024)
The aim of this research is to analyze the development of an integrated area in Bumi Serpong Damai from the perspective of a national strategic project, in relation to land law, the authority of state control rights (HMN) and examine the policies, regulations, management, supervision and impact of control of the area from the verklaring domain side. The research method used is normative juridical where an approach is based on primary law by examining theories, concepts, legal principles and related laws and regulations. The theory used is the Theory of Corporate Social Responsibility. The research results show that the development of the Bumi Serpong Damai integrated area is in accordance with the state's goals, namely the welfare of its people, which is also organized in a strategic government project and is also related to agrarian law. In its implementation, no fraud was found by stakeholders